Evaluating industrial grade functionalized multiwalled carbon nanotubes by X-ray photoelectron spectroscopy. Issue 3 (4th March 2019) - Bagai, Rashmi; Christopher, J.; Kapur, Gurpreet S.
Abstract: Utilization of carbon nanotubes in various applications is a function of their dispersion in respective matrix which effectively depends on the functionalization employed. Functional group distribution on Carbon Nanotube surface is usually a complex mixture of groups depending on the oxidizing agent employed. In this regard, nine varieties of Industrial grade multiwalled carbon nanotubes belonging to 10–30, 20–40 and 50–80 nm outer diameter ranges but differing in functionality (carboxyl and hydroxyl) were analyzed. X-ray photoelectron spectroscopy was employed to quantify the different functionalities on pristine, hydroxyl and carboxyl functionalized multiwalled carbon nanotubes and high-resolution transmission electron microscopy was used to image the internal structure including the side wall damage in functionalized varieties. X-ray photoelectron spectroscopy measurements on nine batches have suggested the presence of carbonyl, carboxyl and hydroxyl functional groups on all multiwalled carbon nanotubes in different proportions. This implies that it is not possible to have exclusive hydroxyl or carboxyl functionalization on a CNT surface Additionally, comparison is drawn between already existing deconvolution procedures from literature.